Hubungan Tingkat Pengetahuan Keluarga Tentang Komunikasi Dengan Penerapan Komunikasi Pada Lansia Di RW 04 Kelurahan Bantargebang - Amara lestari, Viranti; Nur Fajri Hidayati Bunga, Dinda; Suriany Simamora, Rotua (Journal of Pubnursing Sciences, 2024)
Background: lack of communication in the elderly can cause changes in social roles in social interactions in society and in the family. This is supported by the attitude of the elderly who tend to be selfish and reluctant to listen to other people's opinions, resulting in the elderly being socially isolated. In the end, the elderly feel isolated and feel no longer needed because there is no emotional outlet from socializing. Objective: To determine the relationship between the level of family knowledge about communication and the application of communication to the elderly in RW 04, Bantargebang Village. Method: The design in this research uses Observational Analytical with a Cross Sectional research design, using the independent variable the level of family knowledge and the dependent variable the application of communication to the elderly, with a total sample of 70 families with the elderly. The instrument in this research uses a knowledge and application of communication questionnaire. After collecting the data, a statistical test was carried out using Chi Square. Results: Based on the chi square statistical test, the Asymp Significance value was 0.002 (<α (0.05)), this shows that H0 is rejected. Thus, it can be interpreted that there is a relationship between the level of family knowledge about communication and the application of communication to the elderly in RW 04 Bantargebang Village in 2023. Conclusion: There is a relationship between the level of family knowledge about communication and the application of communication to the elderly in RW 04 Bantargebang Village.